Fun Learning Ways in English Class for ESP Students - Wardhani, Norita Prasetya (ICONELT, 2024)
This article explored innovative and interactive teaching methods designed to make the students enjoy when they learn English in a specific Purpose (ESP) class. The writer used qualitative research to analyze the data. The data was taken from open-ended questionnaires and interviews. The writer took random students to be interviewed. The data was taken from fifty mining engineering students who took English classes. According to Conteh (2002, p. 193), "the general atmosphere of the learning, the classroom dynamics, opportunities for student-student and student-teacher interaction, and students’ perception of the teacher’s commitment to their learning" are the factors that influence learners’ attitudes and the learning environment. The findings showed that several activities could make students fun, such as having chit-chat and a friendly teacher, because teaching young learners, the lecturers must be able to have a youthful soul. Then, the interactive teaching-learning process and student-teacher interaction could improve motivation; giving plus points to active students, playing games, watching videos, and outing tasks were fun activities, and the last was classroom discussion with the newest cases. Those activities helped the mining engineering students have more fun in English class.